Hypertension, hyperlipidaemia and thrombophilia as the most common risk factors for retinal vein occlusion in patients under 50 years - Schreiberova, Zuzana; Rehak, Jiri; Babkova, Barbora; Sin, Martin; Rybarikova, Martina; Paskova, Barbora; Sinova, Irena; Hubnerova, Petra; Maluskova, Miroslava; Maresova, Klara; Karhanova, Marta (Biomedical papers, 2024)
Background and Aims. Cardiovascular (CV) diseases are the most common risk factors (RFs) for retinal vein occlusion (RVO) development in general. The aim of this study was to identify the most frequent causes of RVO in patients under 50. Methods. We retrospectively evaluated a group of patients with RVO under 50 years. The parameters of interest included age and sex, RVO type, presence of arterial hypertension (HT), hyperlipidaemia (HLD), diabetes mellitus (DM), congenital thrombophilic disorder (TD), obstructive sleep apnoea syndrome (OSAS), thyroid eye disease (TED), use of hormone contraception (HC) or hormone replacement therapy (HRT), glaucoma and other potential RFs. Patients with central RVO (CRVO), hemi-central RVO (HRVO), branch RVO (BRVO), impending CRVO and combined arterial-venous (AV) occlusion were included. Results. The group consisted of 110 eyes of 103 patients. CV disease was the most common systemic abnormality. 55.3% patients had HT, 17.5% had HLD. TD was the third most frequent RF (12.6%). The cohort also included patients with DM (6.8%), glaucoma (6.8%) and women using HC/HRT (26.2% of female patients). There were isolated cases of RVO due to retinal vasculitis, intense exercise, antiphospholipid syndrome and COVID-19 pneumonia. None of the patients had OSAS, TED or a haemato-oncological disease. The etiology remained unexplained in 20.4% patients. No difference was observed in RF occurrence between patients with CRVO and HRVO and those with BRVO. Conclusion. The most common systemic abnormality in our cohort was CV disease, especially HT and HLD. The risk factors for central, hemi-central and branch RVOs were similar.
Keywords: retinal vein occlusion; risk factors; younger patients; systemic comorbidities; arterial hypertension; hyperlipidaemia; congenital thrombophilic disorder